Smartphones Trigger Depression: A Review of Meta Analysis - Jessica Christina Widhigdo (PSIKODIMENSIA, 2020)
The development of technology and the digital world that is very fast to produce a variety of smart phones with their advantages and uniqueness. The development is increasing the number of smartphones from children, adolescents to adults. The use of smartphone for period of time can lead addiction to smartphone. Difficulties to get rid of smart phones cause teens to deal with anxiety, stress, depression and lead to death. The purpose of this meta-analysis is to find out the relationship between smartphone addiction and depression among adolescents. This meta-analysis involved 14 literatures (2009-2019) with an average age (M = 16.15 years, N = 9895). The results of the meta-analysis found there is positive correlation between depression and smart phones (r = 0.365, p